Clinical and Pregnancy Outcomes of Coronavirus Disease 2019 Among Hospitalized Pregnant Women in the United States. (3rd September 2021) - Ackerman, Christina M; Nguyen, Jennifer L; Ambati, Swapna; Reimbaeva, Maya; Emir, Birol; Cabrera, Javier; Benigno, Michael; Malhotra, Deepa; Hammond, Jennifer; Bahtiyar, Mert Ozan
Abstract: Background: Pregnant women with coronavirus disease 2019 (COVID-19) may be at greater risk of poor maternal and pregnancy outcomes. This retrospective analysis reports clinical and pregnancy outcomes among hospitalized pregnant women with COVID-19 in the United States. Methods: The Premier Healthcare Database—Special Release was used to examine the impact of COVID-19 among pregnant women aged 15–44 years who were hospitalized and who delivered compared with pregnant women without COVID-19. Outcomes evaluated were COVID-19 clinical progression, including the use of supplemental oxygen therapy, intensive care unit admission, critical illness, receipt of invasive mechanical ventilation/extracorporeal membrane oxygenation, maternal death, and pregnancy outcomes, including preterm delivery and stillbirth. Results: Overall, 473 902 hospitalized pregnant women were included, 8584 (1.8%) of whom had a COVID-19 diagnosis (mean age = 28.4 [standard deviation = 6.1] years; 40% Hispanic). The risk of poor clinical and pregnancy outcomes was greater among pregnant women with COVID-19 compared with pregnant women without a COVID-19 diagnosis in 2020; the risk of poor clinical and pregnancy outcomes increased with increasing age. Hispanic and Black non-Hispanic women were consistently observed to have the highest relative risk of experiencing poor clinical or pregnancy outcomes across all age groups. Conclusions: Overall, COVID-19 had a significant negative impact on maternal health and pregnancy outcomes. These data help inform clinical practice and counseling to pregnant women regarding the risks of COVID-19. Clinical studies evaluating the safety and efficacy of vaccines against severe acute respiratory syndrome coronavirus 2 in pregnant women are urgently needed. Abstract : In the United States, COVID-19 has resulted in poor maternal health and pregnancy outcomes, especially among certain race/ethnicity groups and in older women. Educational outreach efforts on infection risks and studies evaluating SARS-CoV-2 vaccines in pregnant women are urgently needed.